2011
DOI: 10.1186/1475-2875-10-50
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of dihydroartemisinin-piperaquine versus artemether-lumefantrine in the treatment of uncomplicated Plasmodium falciparum malaria in Zambian children

Abstract: BackgroundMalaria in Zambia remains a public health and developmental challenge, affecting mostly children under five and pregnant women. In 2002, the first-line treatment for uncomplicated malaria was changed to artemether-lumefantrine (AL) that has proved to be highly efficacious against multidrug resistant Plasmodium falciparum.ObjectiveThe study objective was to determine whether dihydroartemisinin-piperaquine (DHA/PQP) had similar efficacy, safety and tolerability as AL for the treatment of children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 19 publications
8
38
1
Order By: Relevance
“…The 28-day PCR-corrected efficacies for the AL Uíge arm and both DP arms are consistent with previously reported data for AL (24,25) and DP (26,27) and with high clinical efficacy estimates measured in African children prior to the widespread use of ACT. The point estimate for the 28-day PCR-corrected ACPR proportion in the AL Zaire arm of 88.4% is below the 90% WHO target efficacy for first-line treatment policy (12), but the 95% confidence interval of 78 to 95% is wide and includes the 95% secondary WHO target efficacy for ACTs.…”
Section: Screeningsupporting
confidence: 78%
“…The 28-day PCR-corrected efficacies for the AL Uíge arm and both DP arms are consistent with previously reported data for AL (24,25) and DP (26,27) and with high clinical efficacy estimates measured in African children prior to the widespread use of ACT. The point estimate for the 28-day PCR-corrected ACPR proportion in the AL Zaire arm of 88.4% is below the 90% WHO target efficacy for first-line treatment policy (12), but the 95% confidence interval of 78 to 95% is wide and includes the 95% secondary WHO target efficacy for ACTs.…”
Section: Screeningsupporting
confidence: 78%
“…In adults in Thailand, the protective efficacy of DHAPQ was 98% when DHAPQ was administered monthly and 86% when it was administered bimonthly (11). Despite extensive clinical evaluation and use of DHAPQ in Southeast Asia (12,13) and Africa (14)(15)(16), few studies have addressed pharmacokinetics of PQ in children (17)(18)(19). However, one of these studies suggested that children are underdosed with current regimens (17), which was also supported by a recent meta-analysis (20).…”
mentioning
confidence: 86%
“…Several studies using microscopic detection of gametocytes have shown no difference, 2,12,29 an increased risk of gametocyte detection after treatment with AL, 4,11 or more recently, an increased risk of gametocyte detection after treatment with ACT THERAPY, TS PROPHYLAXIS, AND P. FALCIPARUM DP. [14][15][16]30 These differences are likely caused by differences in analyses and the low sensitivity of microscopy for gametocytes. 30 A small study performed in western Kenya found no difference in microscopic gametocyte carriage between treatment with AL or DP.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] However, data comparing the effect of two leading ACTs in Africa-artemether-lumefantrine (AL) and dihyroartemesinin-piperaquine (DP)-on gametocytes have been mixed. 2,4,[11][12][13][14][15][16] Trimethoprim-sulfamethoxazole (TS), a drug routinely used to prevent opportunistic infections in human immunodeficiency virus (HIV) -infected individuals, has been shown to significantly reduce the incidence of malaria. [17][18][19][20][21] However, there is limited data on the association between the use of TS prophylaxis and gametocytes, and several studies have reported an association between exposure to sulfadoxinepyrimethamine (SP), another antifolate drug related to TS, and an increased prevalence and density of gametocytes.…”
Section: Introductionmentioning
confidence: 99%